Poverty as Public Policy: A Reflection from the Perspective of Political Science - Hernández Ortiz, Evelyn (2008)
This article reflects on how the Pacheco de la Espriella and Arias Sánchez administrations have addressed the issue of poverty as a public policy on the national political agenda, drawing on conceptual contributions from political science. The article consists of three sections. The first conceptualizes economic policy as a public policy that seeks general economic well-being and, as such, enables government authorities to make decisions regarding poverty. The second section addresses the role of the Economic and Social Councils, their involvement in the formulation of economic policy, and the actions that have been taken in recent years in Costa Rica. Finally, the article develops some ideas on the treatment of poverty as a public policy issue, drawing on actions implemented during the 2002–2006 period and from 2006 to the present.